Negative active material, preparation thereof, negative pole piece, secondary battery and device
By forming a composite layer of carbon-based material and metal oxide on the surface of the silicon-based material, the problem of insufficient electron conduction and ion conduction performance of the silicon-based negative electrode material is solved, and efficient power battery performance improvement is achieved.
Patent Information
- Application Number
- CN202310880045.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-17
- Publication Date
- 2025-01-17
AI Technical Summary
The existing silicon-based anode materials have insufficient electron conduction performance in power batteries, and the interface layer disadvantages of the dual-interface layer coating method are superimposed, making it difficult to simultaneously improve electron conduction and ion conduction performance.
The composite layer of carbon-based materials and metal oxides (such as titanium, aluminum, molybdenum, vanadium) is used to coat silicon-based particles, promote ion conduction through small-particle metal oxides, and use carbon-based materials to compensate for insufficient electron conduction to form an efficient Composite layer.
The excellent electron conduction and ion conduction properties of the negative electrode material are achieved, the reaction kinetics and stability are improved, and the low electron conduction and ion conduction properties in traditional methods are avoided.
Smart Images

Figure CN119324207A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of energy storage, and specifically to a negative electrode active material, its preparation, a negative electrode plate, a secondary battery and a device. Background Art
[0002] The development of electric vehicles has gradually become an important way to save energy and reduce emissions. As the core component of electric vehicles, the energy density of power batteries directly affects the vehicle's range and the user's travel experience. At present, the negative electrode material of power batteries is mainly graphite material, and its specific capacity is close to the theoretical value of 372mAh / g. Therefore, finding the next generation of negative electrode materials has become the key to improving the energy density of power batteries. Silicon oxide SiOx (0≤x≤2) has become the best candidate due to its high theoretical specific capacity, low lithium insertion potential (<0.5V) and abundant reserves. However, problems such as slow kinetics, large volume expansion, and unstable SEI film of SiOx materials have seriously affected their commercial application.
[0003] In this regard, there is a method in the prior art for carbon coating of silicon-based materials to improve their electronic conductivity. For example, SiOx is coated with multi-walled carbon nanotubes / N-doped carbon, and the equivalent series resistance of the target material obtained is more than 4 times smaller than that of pure SiOx, and the capacity is 388mAh / g at a current density of 800mA / g (Li et al., Electrochimica Acta, 2016, 206, 328-336). Although carbon coating significantly improves electronic conduction, it has limited contribution to ionic conduction.
[0004] In order to improve ion conduction, patent CN 113036135 A proposes double interface layer coating, the first coating layer is titanium oxide, which is used to improve the first coulomb efficiency and ion conductivity of the composite negative electrode material, and the second coating layer is a conductive carbon layer, which is used to improve the electronic conductivity. However, this double interface layer coating also superimposes the shortcomings of each interface layer, such as the slow electronic conduction of the titanium oxide layer and the limited ion conduction of the conductive carbon layer.
[0005] Therefore, there is an urgent need in the art for a negative electrode active material comprising a silicon-based material, which has not only significantly improved electronic conductivity but also excellent ion conductivity. Summary of the invention
[0006] In order to solve the above problems, the object of the present invention is to provide a negative electrode active material, especially a silicon-based negative electrode active material, which not only has a desired capacity but also ensures electronic conductivity and ion conductivity.
[0007] In a first aspect of the present invention, a negative electrode active material is provided, which includes silicon-based particles and a composite layer located on the surface of the silicon-based particles, the composite layer includes a carbon-based material and a metal oxide distributed in the carbon-based material, and the metal oxide includes at least one of titanium, aluminum, molybdenum and vanadium.
[0008] According to one embodiment of the present invention, the mass ratio of carbon element to metal element in the composite layer is 0.02 to 300, preferably 1 to 200, preferably 3 to 198, and preferably 18 to 85.
[0009] According to one embodiment of the present invention, the mass ratio of the composite layer to the silicon-based particles is 0.02 to 4, preferably 0.1 to 3.5, preferably 0.2 to 1.8.
[0010] According to one embodiment of the present invention, the carbon-based material includes hard carbon or soft carbon, preferably hard carbon, the metal oxide includes at least one of titanium oxide, aluminum oxide, molybdenum oxide and vanadium oxide, and the silicon-based particles include silicon-oxygen particles or silicon-carbon particles.
[0011] According to one embodiment of the present invention, the Dv50 of the silicon-based particles is 0.2 μm to 15 μm, and preferably the Dv50 of the silicon-based particles is 1 μm to 5 μm.
[0012] According to one embodiment of the present invention, the thickness of the composite layer is 100 nm to 2000 nm, preferably 130 nm to 1650 nm, preferably 150 nm to 800 nm.
[0013] According to one embodiment of the present invention, the metal oxide includes at least one of titanium and vanadium.
[0014] According to one embodiment of the present invention, the silicon oxide particles are SiOx, wherein 0.5≤x≤2, preferably 0.5≤x≤1.5. The molecular formula SiOx of the silicon oxide particles in the present invention refers to the average molecular composition of the silicon oxide particles.
[0015] According to one embodiment of the present invention, the composite layer comprises metal oxides formed by the metal elements, in particular metal oxide particles, and the average particle size of the metal oxide particles is 5 nm to 50 nm.
[0016] According to one embodiment of the present invention, the composite layer comprises a carbon-based material.
[0017] According to one embodiment of the present invention, the composite layer is composed of a carbon-based material and a metal oxide distributed or embedded in the carbon-based material.
[0018] According to one embodiment of the present invention, the content of the carbon-based material is 50 wt % to 95 wt %, preferably 70 wt % to 90 wt %, based on the total weight of the composite layer.
[0019] According to one embodiment of the present invention, the content of the metal oxide is 5 wt % to 50 wt %, preferably 10 wt % to 30 wt %, based on the total mass of the composite layer.
[0020] According to one embodiment of the present invention, the metal oxide includes at least one of titanium oxide, aluminum oxide, molybdenum oxide and vanadium oxide, and these oxides have an average particle size of 5nm to 50nm. In particular, the metal oxide is uniformly distributed in the composite layer, especially evenly distributed in the carbon-based material.
[0021] According to one embodiment of the present invention, the carbon-based material includes hard carbon obtained by pyrolysis of at least one of polyvinyl pyrrolidone, glucose, and sucrose. In a preferred embodiment, the thickness of the hard carbon layer is 100nm to 1000nm. In another preferred embodiment, the carbon-based material has an amorphous structure.
[0022] By distributing small-particle metal oxides in carbon-based materials to form a composite layer, the negative electrode active material according to the present invention has excellent ion conduction and electronic conduction properties at the same time, and is not constrained by existing theories. This may be because small-particle metal oxides can promote ion conduction after lithium insertion in the negative electrode, and the lack of electronic conduction brought by metal oxides is usually compensated by the surrounding carbon-based materials. Therefore, the negative electrode active material according to the present invention has high ion conduction performance brought by metal oxides and high electronic conduction performance brought by carbon-based materials, and surprisingly avoids the low electronic conduction performance caused by the use of metal oxides in the prior art, and the low ion conduction performance caused by the use of carbon-based materials.
[0023] According to one embodiment of the present invention, the composite layer is a composite layer of carbon-based materials and inorganic metal oxides, wherein the carbon in the composite layer can improve the electronic conductivity of the negative electrode active material, and the inorganic metal compound particles embedded in the carbon are converted into corresponding lithium compounds after the first lithium insertion, thereby improving the ionic conductivity of the composite layer, thereby greatly improving the reaction kinetics. In addition, the composite layer can also alleviate the pulverization of the silicon-based material during the cycle process, stabilize the SEI film on the surface, and effectively improve the stability of the negative electrode active material.
[0024] According to one embodiment of the present invention, the metal element is at least one of Ti and V.
[0025] According to one embodiment of the present invention, the Dv50 of the silicon-based particles is 1 μm to 5 μm, and the metal element is Ti.
[0026] In a second aspect of the present invention, there is provided a method for preparing a negative electrode active material, the method comprising the following steps:
[0027] (a) mixing a dispersion of silicon-based particles, a carbon source and an inorganic metal precursor to form a dispersion;
[0028] (b) heating the dispersion obtained in step (a) at a temperature of 80° C. to 150° C., preferably 90° C. to 120° C., to evaporate the solvent and obtain a gel;
[0029] (c) subjecting the gel obtained in step (b) to an annealing treatment at a temperature of 700° C. to 1100° C., preferably 800° C. to 1000° C., to obtain the negative electrode active material.
[0030] The negative electrode active material obtained by the method according to the present invention is a silicon-based (SiOx) material coated with a carbon / inorganic metal compound composite layer. Among them, the carbon in the composite layer can improve the electronic conductivity of the composite material, and the nano-inorganic particles embedded in the carbon are converted into corresponding lithium compounds after the first lithium insertion, so that the ionic conductivity of the composite layer can be improved, thereby greatly improving the reaction kinetics. In particular, by controlling the heating temperature and annealing temperature in the method of the present invention, the decomposition rate of the inorganic metal precursor can be effectively adjusted, thereby controlling the particle size of the metal oxide in the composite layer. In addition, the composite layer can also alleviate the pulverization of the silicon-based material during the cycle, stabilize the SEI film on the surface, and effectively improve the stability of the silicon-based material.
[0031] According to one embodiment of the present invention, the carbon source includes at least one of polyvinyl pyrrolidone, glucose and sucrose.
[0032] According to one embodiment of the present invention, the inorganic metal precursor includes at least one of tetraisopropyl titanate, tetrabutyl titanate, aluminum nitrate, sodium molybdate, and sodium metavanadate.
[0033] According to one embodiment of the present invention, the mass ratio of the carbon source to the silicon-based particles is 0.05 to 10, preferably 0.5 to 2.
[0034] According to one embodiment of the present invention, the mass ratio of the inorganic metal precursor to the silicon-based particles is 0.01 to 1, preferably 0.05 to 0.5.
[0035] According to one embodiment of the present invention, the Dv50 of the silicon-based particles is 0.2 μm to 15 μm, preferably 1 μm to 5 μm, and particularly preferably 2.5 μm to 5 μm.
[0036] According to one embodiment of the present invention, the solvent is at least one of deionized water and anhydrous ethanol.
[0037] According to one embodiment of the present invention, in step (a), the silicon-based particles are dispersed in the solvent by means of ultrasonic dispersion, and the ultrasonic dispersion time is 5 min to 60 min, preferably 10 min to 15 min.
[0038] According to one embodiment of the present invention, in step (c), the duration of the annealing treatment is 0.5 h to 5 h, preferably 2 h to 3 h.
[0039] According to one embodiment of the present invention, in step (c), the annealing treatment is performed under an annealing atmosphere, and the annealing atmosphere includes at least one of a hydrogen-argon mixed gas, nitrogen, argon, and ammonia.
[0040] In a third aspect of the present invention, a negative electrode plate is provided, the negative electrode plate comprising a negative electrode current collector, a negative electrode material layer is arranged on the negative electrode current collector, the negative electrode material layer comprises the negative electrode active material according to the first aspect; and / or a negative electrode material layer is arranged on the negative electrode current collector, the negative electrode material layer comprises the negative electrode active material prepared by the method described in the second aspect.
[0041] In a fourth aspect of the present invention, a secondary battery is provided. The secondary battery comprises a positive electrode sheet, an electrolyte, a separator and the negative electrode sheet of the third invention.
[0042] In a fifth aspect of the present invention, a device is provided, the device comprising the secondary battery according to the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] In order to make the above-mentioned purpose, features and advantages of the present invention easier to understand, the specific implementation methods of the present invention are described in detail below in conjunction with the accompanying drawings. In the following description, many specific details are set forth to fully understand the present invention, but the present invention can also be implemented in other ways different from those described herein, so the present invention is not limited to the specific embodiments disclosed below.
[0045] Figure 1 Schematically shows a TEM image of a negative electrode active material according to the present invention;
[0046] Figure 2 The electrochemical performance of the electrochemical device according to the present invention is schematically shown. DETAILED DESCRIPTION
[0047] In order to make the purpose, technical scheme and advantages of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present application, rather than all the embodiments. The relevant embodiments described herein are illustrative and used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application. All other embodiments obtained by those skilled in the art based on the technical scheme provided by the present application and the embodiments given belong to the scope of protection of the present application.
[0048] Unless otherwise specified, the terms used in this application have the commonly known meanings generally understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the examples of this application).
[0049] A list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single component or multiple components. Item B may contain a single component or multiple components. Item C may contain a single component or multiple components.
[0050] The term "Dv50" refers to the particle size corresponding to when the cumulative particle size volume distribution percentage reaches 50%.
[0051] 1. Negative electrode
[0052] According to some embodiments of the present application, a negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, wherein the negative electrode active material layer includes a conductive agent, a binder and a negative electrode active material according to the present invention.
[0053] In some embodiments, the negative electrode active material includes silicon-based particles, the surface of the silicon-based particles is coated with a composite layer, the composite layer contains carbon elements and metal elements, the metal elements include at least one of Ti, Al, Mo and V, and wherein the Dv50 of the silicon-based particles is 0.2μm to 15μm, the thickness of the composite layer is 100nm to 1000nm, and the silicon-based particles are SiOx, wherein 0.5≤x≤2.
[0054] In some embodiments, in addition to the negative electrode active material according to the present invention, the negative electrode active coating may also contain commonly used negative electrode active materials, including but not limited to: graphite, carbon materials, silicon-based materials, metal oxides, and tin-based materials. For example, silicon-based composite materials include but are not limited to silicon-carbon composite materials, silicon-metal oxide composite materials, and silicon alloy composite materials. For example, metal oxides include but are not limited to iron oxide, lithium titanate, copper oxide, etc., which are regarded as all metal oxides that can be used for lithium extraction and storage.
[0055] In some embodiments, the conductive agent can be a commonly used conductive agent, including but not limited to: metal-based materials, carbon-based materials, conductive polymers and mixtures thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, nickel, copper, aluminum or silver. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, Super P, acetylene black, Ketjen black, carbon black, carbon fiber or any combination thereof. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0056] In some embodiments, the binder can be a commonly used binder, including but not limited to: polyvinyl alcohol, hydroxypropyl cellulose, sodium carboxymethyl cellulose (CMC), diacetyl cellulose, ethylene oxide-containing polymers, carboxylated polyvinyl chloride, polyvinyl pyrrolidone, polyurethane, polyvinyl chloride, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0057] 2. Positive electrode
[0058] The materials, compositions and manufacturing methods of the positive electrode that can be used in the embodiments of the present application include any technology disclosed in the prior art.
[0059] According to some embodiments of the present application, the positive electrode includes a current collector and a positive electrode active material layer located on the current collector. According to some embodiments of the present application, the positive electrode active material includes, but is not limited to: lithium cobalt oxide (LiCoO2), lithium nickel cobalt manganese (NCM) ternary material, lithium nickel cobalt aluminum (NCA) ternary material, lithium iron phosphate (LiFePO4), lithium iron manganese phosphate (LiMn x Fe 1- x PO4) or lithium manganate (LiMn2O4).
[0060] According to a preferred embodiment of the present application, the positive electrode active material is Li[Ni 1-x-y Co x M y ]O2(M=Mn, Al, etc., such as lithium nickel cobalt manganese oxide Li[Ni 1-x-y Co xMn y ]O2, 1-xy ≥ 0.5, lithium nickel cobalt aluminum oxide Li[Ni 1-x-y Co x Al y ]O2, 1-xy≥0.5).
[0061] According to some embodiments of the present application, the positive electrode active material layer also includes a binder and optionally includes a conductive material. The binder improves the bonding between the positive electrode active material particles and also improves the bonding between the positive electrode active material and the current collector. In some embodiments, the binder includes: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin or nylon, etc.
[0062] According to some embodiments of the present application, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0063] 3. Diaphragm
[0064] The material and shape of the separator used in the embodiments of the present invention are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or an inorganic substance formed of a material that is stable to the electrolyte of the present invention.
[0065] For example, the diaphragm may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene and polyethylene terephthalate. Specifically, polypropylene porous film, polyethylene porous film, polypropylene non-woven fabric, polyethylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film can be selected.
[0066] A surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0067] The inorganic layer includes inorganic particles and a binder, wherein the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.
[0068] The polymer layer contains polymers, and the polymer material is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyethylene alkoxide, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).
[0069] In a preferred embodiment according to the present invention, the separator is a polyethylene (PE) separator coated with ceramic layers on both sides, wherein the PE layer thickness is in the range of 5 to 20 μm, and the coating thickness of each ceramic layer is in the range of 0 to 5 μm.
[0070] 4. Electrolyte
[0071] In some embodiments, the electrolyte includes a lithium salt and a solvent.
[0072] In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium difluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(oxalatoborate), or lithium difluorooxalatoborate.
[0073] In some embodiments, the solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate, ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0074] In a preferred embodiment according to the present invention, the electrolyte is LiPF6 / EC+DMC+EMC.
[0075] 5. Secondary battery
[0076] The secondary battery according to the present invention is, for example, a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0077] The electrochemical device according to the present invention can be used in devices including, but not limited to, laptop computers, pen-type computers, mobile computers, electronic book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini CDs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, large household batteries and lithium-ion capacitors, etc.
[0078] 6. Button half battery
[0079] The button half-cell mentioned in the present invention is a CR2016 type button half-cell, which is assembled by the following steps:
[0080] A metallic lithium sheet was used as the counter electrode; 1M LiPF6 / EC:DEC:DMC (1:1:1) was used as the electrolyte; a Celgard 2400 polypropylene microporous membrane was used as the separator; the negative electrode active material, Super P, and sodium carboxymethyl cellulose (CMC) were dispersed in deionized water in a mass ratio of 80:10:10, stirred evenly, and then placed on a 6 μm thick Cu foil and placed in a vacuum drying oven at 110°C for 2 h to prepare a working electrode.
[0081] All cells were assembled in a glove box filled with Ar gas.
[0082] 7. Testing
[0083] The electrochemical performance test was carried out using the battery test equipment Land CT2001 A, with a voltage window of 0.005-3.0V and a pole piece loading of 1±0.05g / cm 2 .
[0084] The method for determining the buckling performance of lithium-ion batteries is as follows:
[0085] Determination of the first coulombic efficiency: At 25°C, the prepared lithium ion secondary battery is discharged to 0.005V at a current density of 100mA / g, and the initial discharge capacity is recorded. After standing for 5 minutes, it is charged to 3.0V at a current density of 100mA / g, and the initial charge capacity is recorded. The first coulombic efficiency performance test of the lithium ion secondary battery = initial charge capacity / initial discharge capacity × 100%.
[0086] Determination of rate capacity: At 25°C, the prepared lithium-ion secondary battery was discharged to 0.005V at a current density of 200mA / g or 2000mA / g. After standing for 5 minutes, it was charged to 3.0V at a current density of 200mA / g or 2000mA / g, and the charging capacity was recorded, which was the specific capacity at the rate.
[0087] Cycle capacity retention rate: At 25°C, discharge the prepared lithium-ion secondary battery to 0.005V at a current density of 1000mA / g, and record the discharge capacity. After standing for 5 minutes, charge it to 3.0V at a current density of 1000mA / g, and record the charge capacity. Charge and discharge the lithium-ion secondary battery 100 times using the above method, and record the discharge capacity each time. The capacity retention rate of the lithium-ion secondary battery after 100 cycles at 25°C = 100th charge capacity / initial charge capacity × 100%.
[0088] Examples and Comparative Examples
[0089] Example 1
[0090] Preparation of lithium-ion battery (half-cell):
[0091] (1) Preparation of negative electrode sheet
[0092] The negative electrode active material, super P and CMC were homogenized in a mass ratio of 80:10:10 to obtain a uniformly dispersed slurry, which was coated on a 6 μm copper foil. The negative electrode active material loading was 1.0 mg / cm 2 The preparation of the negative electrode active material is as follows:
[0093] (a) 1g D V 50 SiOx (x is 0.8-1.2) particles with a size of 2.5 μm were ultrasonically dispersed in a beaker containing 20 mL of ethanol, 1 g of polyvinyl pyrrolidone and 0.1 g of tetrabutyl titanate were added under stirring, and a uniform dispersion was formed after stirring for 30 min;
[0094] (b) placing the beaker containing the dispersion prepared in step (a) in an oil bath at 100° C., stirring until the solvent is completely evaporated, taking out the beaker and collecting the gel powder;
[0095] (c) The gel powder obtained in step (b) is placed in a porcelain ark, and then placed in a tube furnace, introduced into a nitrogen atmosphere, and annealed at 900° C. for 2 h. After cooling to room temperature, a negative electrode active material is obtained.
[0096] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 15, the mass ratio of the composite layer to SiOx particles is 0.27, and the thickness of the composite layer is about 150 nm.
[0097] (2) Preparation of button half-cell (CR2016 type button half-cell)
[0098] A metal lithium sheet is used as a counter electrode; 1M LiPF6 / EC:DEC:DMC (1:1:1) is used as an electrolyte; a Celgard 2400 polypropylene microporous membrane is used as a diaphragm; and the button half-cell of the invention is assembled in a glove box filled with Ar gas.
[0099] Example 2
[0100] Example 2 was carried out with reference to Example 1, except that, in Example 2, in the step (a) of preparing the negative electrode active material, 0.05 g of tetrabutyl titanate was added.
[0101] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 28, the mass ratio of the composite layer to SiOx particles is 0.26, and the thickness of the composite layer is about 145 nm.
[0102] Example 3
[0103] Example 3 was carried out with reference to Example 1, except that, in Example 3, 0.2 g of tetrabutyl titanate was added in the step (a) of preparing the negative electrode active material.
[0104] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 8, the mass ratio of the composite layer to SiOx particles is 0.29, and the thickness of the composite layer is about 160 nm.
[0105] Example 4
[0106] Example 4 is carried out with reference to Example 1, except that, in Example 4, the preparation step (a) of the negative electrode active material is as follows:
[0107] 1g D V 50 SiOx (x is 0.8-1.2) particles with a size of 2.5 μm were ultrasonically dispersed in a beaker containing 20 mL of ethanol, and 1 g of glucose and 0.1 g of sodium metavanadate were added under stirring. After stirring for 30 min, a uniform dispersion was formed.
[0108] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 5, the mass ratio of the composite layer to SiOx particles is 0.30, and the thickness of the composite layer is about 140 nm.
[0109] Example 5
[0110] Example 5 was carried out with reference to Example 1, except that, in Example 5, 5 g of polyvinyl pyrrolidone was added in the step (a) of preparing the negative electrode active material.
[0111] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 80, the mass ratio of the composite layer to SiOx particles is 1.5, and the thickness of the composite layer is about 780 nm.
[0112] Example 6
[0113] Example 6 was carried out with reference to Example 1, except that, in Example 6, 10 g of polyvinyl pyrrolidone was added in the step (a) of preparing the negative electrode active material.
[0114] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 195, the mass ratio of the composite layer to SiOx particles is 3, and the thickness of the composite layer is about 1600 nm.
[0115] Example 7
[0116] Example 7 was carried out with reference to Example 1, except that, in Example 7, in the step (a) of preparing the negative electrode active material, 1 g of glucose and 0.1 g of aluminum nitrate were added.
[0117] The mass ratio of carbon element to metal element in the composite layer of the prepared negative electrode active material is 20, the mass ratio of the composite layer to SiOx particles is 0.27, and the thickness of the composite layer is about 135 nm.
[0118] Comparative Example 1
[0119] Comparative Example 1 was carried out with reference to Example 1, except that, in Comparative Example 1, the negative electrode active material was prepared as follows:
[0120] 1 g of SiOx (x is 0.8-1.2) particles with a Dv50 of 2.5 μm were placed in a porcelain ark, then placed in a tube furnace, introduced into a nitrogen atmosphere, and annealed at 900°C for 2 h. After cooling to room temperature, the negative electrode active material was obtained.
[0121] Comparative Example 2
[0122] Comparative Example 2 was carried out with reference to Example 1, except that, in Comparative Example 2, the negative electrode active material was prepared as follows:
[0123] (a) 1 g of SiOx (x is 0.8-1.2) particles with a Dv50 of 2.5 μm were ultrasonically dispersed in a beaker containing 20 mL of ethanol, and 1.1 g of tetrabutyl titanate was added under stirring. After stirring for 30 min, a uniform dispersion was formed.
[0124] (b) placing the beaker containing the dispersion prepared in step (a) in an oil bath at 100° C., stirring until the solvent is completely evaporated, taking out the beaker and collecting the gel powder;
[0125] (c) The gel powder obtained in step (b) is placed in a porcelain ark, and then placed in a tube furnace, introduced into a nitrogen atmosphere, and annealed at 900° C. for 2 h. After cooling to room temperature, a negative electrode active material is obtained.
[0126] The mass ratio of the composite layer of the prepared negative electrode active material to the SiOx particles is 0.25, and the thickness of the composite layer is about 60 nm.
[0127] Figure 1 The TEM image of the negative electrode active material obtained from Example 1 is shown in Figure 1. It can be seen that a carbon / titanium oxide composite coating layer with a thickness of about 150 nm is coated on the surface of the SiOx particles, in which titanium oxide nanoparticles are evenly distributed in the carbon, and the size of the titanium oxide nanoparticles is about 10 nm. After the lithium insertion reaction occurs, the titanium oxide can be converted in situ into the fast ion conductor lithium titanate; at the same time, the rich lithium titanate / carbon grain boundaries can further improve the ion diffusion rate, and cooperate with the excellent electron transport ability of carbon, so that the negative electrode active material exhibits excellent electrochemical reaction kinetics.
[0128] Button half-cells were prepared using the negative electrode active materials obtained from Examples 1-5 and Comparative Examples 1-2, and the electrochemical performance of each button half-cell was tested, wherein the cycle capacity retention rate refers to the cycle capacity retention rate after 100 cycles at a current density of 1000 mA / g, that is, the capacity retention rate after 100 cycles = 100th discharge capacity / first discharge capacity. The test results are shown in Table 1.
[0129] Table 1
[0130]
[0131] As can be seen from Table 1, the battery prepared using the negative electrode active material according to the present invention obtains the desired electrochemical performance, while the batteries prepared using the negative electrode active materials of Comparative Example 1 and Comparative Example 2 obtain poor electrochemical performance due to poor electronic conductivity and instability, as shown in Figure 2 As shown in FIG. 1 , the negative electrode active material of Comparative Example 1 has almost no capacity contribution at a current density of 500 mA / g or above.
[0132] Although some exemplary embodiments of the present application have been illustrated and described, the present application is not limited to the disclosed embodiments. On the contrary, those skilled in the art will recognize that some modifications and changes may be made to the described embodiments without departing from the spirit and scope of the present application as described in the appended claims, and these modifications and changes also fall within the scope of protection of the present invention.
Claims
1. A negative electrode active material, characterized in that: The negative electrode active material includes silicon-based particles and a composite layer located on the surface of the silicon-based particles, the composite layer includes a carbon-based material and a metal oxide distributed in the carbon-based material, and the metal oxide includes at least one of titanium, aluminum, molybdenum and vanadium.
2. The negative electrode active material according to claim 1, characterized in that The mass ratio of carbon element to metal element in the composite layer is 0.02 to 300, preferably 1 to 200, and / or; The mass ratio of the composite layer to the silicon-based particles is 0.02 to 4.
3. The negative electrode active material according to claim 1, characterized in that The carbon-based material comprises hard carbon or soft carbon, and / or; The metal oxide includes at least one of titanium oxide, aluminum oxide, molybdenum oxide and vanadium oxide, and / or The silicon-based particles include silicon-oxygen particles or silicon-carbon particles.
4. The negative electrode active material according to claim 3, characterized in that The metal oxide is uniformly distributed in the carbon-based material, and / or The silicon oxide particles are SiOx, wherein 0.5≤x≤2, preferably 0.5≤x≤1.
5.
5. The negative electrode active material according to claim 1, characterized in that Satisfy at least one of the following: (i) the Dv50 of the silicon-based particles is 0.2 μm to 15 μm, preferably 1 μm to 5 μm, (ii) the thickness of the composite layer is 100 nm to 2000 nm, preferably 130 nm to 1650 nm, (iii) The metal oxide includes at least one of titanium and vanadium.
6. A method for preparing a negative electrode active material according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: (a) mixing a dispersion of silicon-based particles, a carbon source and an inorganic metal precursor to form a dispersion; (b) heating the dispersion obtained in step (a) at a temperature of 80° C. to 150° C., preferably 90° C. to 120° C., to evaporate the solvent and obtain a gel; (c) subjecting the gel obtained in step (b) to an annealing treatment at a temperature of 700° C. to 1100° C., preferably 800° C. to 1000° C., to obtain the negative electrode active material.
7. The method according to claim 6, characterized in that The carbon source comprises at least one of polyvinyl pyrrolidone, glucose and sucrose; and / or The inorganic metal precursor includes at least one of tetraisopropyl titanate, tetrabutyl titanate, aluminum nitrate, sodium molybdate, and sodium metavanadate; and / or The mass ratio of the carbon source to the silicon-based particles is 0.05 to 10, and / or The mass ratio of the inorganic metal precursor to the silicon-based particles is 0.01 to 1; and / or The silicon-based particles have a Dv50 of 0.2 μm to 15 μm.
8. A negative electrode plate, characterized in that: The negative electrode plate comprises a negative electrode current collector, a negative electrode material layer is arranged on the negative electrode current collector, and the negative electrode material layer comprises the negative electrode active material according to claim 1; and / or a negative electrode material layer is arranged on the negative electrode current collector, and the negative electrode material layer comprises the negative electrode active material prepared by the method according to claim 6.
9. A secondary battery, characterized in that: The secondary battery comprises the negative electrode sheet, the positive electrode sheet, the electrolyte and the separator as claimed in claim 8.
10. A device comprising the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Composite negative electrode material and preparation method thereof, pole piece, battery and device
CN113036135A